Soil–water characteristic curve and permeability function of recycled concrete aggregates coated with oil or wax - Rahardjo, Harianto (2019)
Recycled concrete aggregate (RCA) is known to be a hydrophilic material. Anattempt has been made to convert RCA into a hydrophobic material by coatingit separately with oil or wax. Both oil and wax are known to increase thehydrophobicity of soil. Although the soil–water characteristic curve (SWCC) andpermeability function of coarse-grained aggregates have been investigated, theeffect of the introduction of hydrophobicity (coating it with oil or wax) into thecoarse aggregates to their SWCC and permeability function has not been fullyunderstood. The SWCC indicates that coating RCA with oil or wax modifies thedrying and wetting curves as compared with RCA without any coating. The air-entry values and water-entry values are also modified upon coating. RCAs coatedwith oil or wax were found to prevent ingress of water during the wetting test forSWCC. The permeability function of RCAs is also modified.